Domain 15 of the serine proteinase inhibitor LEKTI blocks HIV infection in vitro (Medical Journal of Indonesia, 2013)
Background: Lympho-epithelial Kazal-type-related inhibitor (LEKTI) is a 15-domain serine proteinase inhibitor, parts of which have first been isolated from human blood filtrate. It is encoded by the gene SPINK5. In the past, different groups reported antiviral activities of certain serine proteinase inhibitors, such as mucous proteinase inhibitor and alpha1-proteinase inhibitor. The purpose of this study was to test two representative domains of the proteinase inhibitor LEKTI for anti-HIV activities. Methods: LEKTI domains 6 and 15 were recombinantly produced in E.coli. To test their inhibitory activity against HIV infection, the reporter cell line P4-R5 MAGI carrying an HIV-inducible reporter gene was infected by a CCR5-tropic HIV strain in the presence of different inhibitor concentrations. After three days, infection rates were determined by quantifying ß-galactosidase activities using the Galacto-Light Plus™ ß-Galactosidase Reporter Gene Assay. Results: In contrast to LEKTI domain 6, LEKTI domain 15 suppressed HIV-induced reporter gene activities with an IC50 value of approximately 29 μM. Conclusion: LEKTI domain 15 represents an inhibitor of HIV infection.